Holding momentum: a grounded theory study of strategies for sustaining living at home in older persons. Issue 1 (1st January 2019) - Hatcher, Deborah; Chang, Esther; Schmied, Virginia; Garrido, Sandra
ABSTRACT: Purpose : Government strategies are putting increasing emphasis on sustaining the capacity of older persons to continue living independently in their own homes to ease strain on aged care services. The aim of this study was to understand the experiences and strategies that older people utilize to remain living at home from their own perspective. Methods : A grounded theory methodology was used to explore the actions and strategies used by persons over the age of 65 to enable them to remain living in their own homes. Data were collected from 21 women and men in three focus group discussions and 10 in-depth semi-structured interviews. Results : The data revealed that the central process participants used to hold momentum and sustain living at home involves a circular process in which older people acknowledge change and make ongoing evaluations and decisions about ageing at home. Conclusion : These findings have implications for informing policy and service provision by identifying appropriate resources and services to promote successful ageing at home.